Süreyya-Dani technique, a new technique to address notching of soft triangle and opening external nasal valve - Omer, Goran Latif; Şeneldir, Süreyya; Di Girolamo, Stefano; Habibullah, Imad J.; Ahmed, Avar F.; Ali, Sahand S.; Abdullah, Aland S.; Mustafa, Ayman M.; Abdalla, Berun A.; Hassan, Hemin Noori; Mohammed, Shvan H.; Kakamad, Fahmi H. (Frontiers in Surgery, 2024)
Introduction While different methods are employed for fixing narrowed nasal valves and preventing the notching of soft triangles, this study aims to demonstrate the effectiveness of a new technique called Süreyya-Dani Technique. Methods This prospective study composed 100 patients who underwent rhinoplasty using the Süreyya-Dani technique. All patients presented with either notching of the soft triangle and/or external nasal valve dysfunction. Patients with the absence of soft triangle notching and external nasal valve dysfunction were excluded from this study. Facial analysis was conducted for all patients to identify any asymmetry in the face, and all nasal defects were identified. Descriptive statistics were calculated for different variables. Analytical statistics, namely Chi-Square test, was conducted with a significance level set at P < 0.05. Results In the current study, 100 patients were involved, out of which 63 (63%) were female and 37 (37%) were male. The participants' ages ranged from 18 to 46 years, with a mean age of 30 years. various chief complaints were found among patients, with the majority 37(37%) expressing cosmetic concerns. A statistically significant difference was found for the association of nasal tip defects with genders, intraoperative findings, and chef complaints, and the association between the degree of external valve insufficiency and crural weakness (P-value < 0.05). Conclusion Despite many techniques that have been put forward to fix narrowed nasal valves and prevent notching of the soft triangle, the Süreyya-Dani Technique could work to prevent its occurrence successfully.